2017
DOI: 10.5539/elt.v10n7p78
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Critical Thinking from University EFL Teachers

Abstract: Critical Thinking has become an educational and social ideal. English as a Foreign Language (EFL) teaching has not been apart from the discussion on the importance of implementing Critical Thinking into the educational process. However, research on Critical Thinking has broadly been carried out in other fields of knowledge rather than in EFL. Therefore, this study aimed to comprehend the conceptions university English teachers had about Critical Thinking in order to get a wider understanding on the way it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 7 publications
1
39
0
1
Order By: Relevance
“…In consequence, role-play can be incorporated successfully to educational programs that use teaching strategies to stimulate horizontal communication and inside of informal learning environments (Erturk, 2015). Role play is a technique that allows students learn through the simulation of different situations, working in groups for putting on scene discussions, tasks and tests to improve students' performances since a joinable act (Marin & De la Pava, 2017).…”
Section: Role-play In the Foreign Language Classmentioning
confidence: 99%
“…In consequence, role-play can be incorporated successfully to educational programs that use teaching strategies to stimulate horizontal communication and inside of informal learning environments (Erturk, 2015). Role play is a technique that allows students learn through the simulation of different situations, working in groups for putting on scene discussions, tasks and tests to improve students' performances since a joinable act (Marin & De la Pava, 2017).…”
Section: Role-play In the Foreign Language Classmentioning
confidence: 99%
“…These tasks are very useful in teaching writing skills. Marin and Pava (2017) state that promoting critical thinking tasks (CTTs) in EFL requires teachers to think about teaching beyond grammatical structures and vocabulary, and focus on fostering thinking, creativity, autonomous learning, decision-making and self-evaluation. Likewise, educators should provide opportunities for students to be creative and study in a real communicative environment in which students freely express their points of view about topics discussed in class.…”
Section: The Application Of Critical Thinking Tasks In Language Educamentioning
confidence: 99%
“…Even at the present time, its definition has broad parameters and lacks consensus over its meaning. Marin & Pava (2017) investigated university English language teachers' view on critical thinking in the Colombian context. The findings showed that critical thinking is mainly considered as problem solving, which comprises higher order thinking skills.…”
Section: Critical Thinkingmentioning
confidence: 99%
“…The findings showed that critical thinking is: 1) judgement; 2) a skeptical and provisional view of knowledge; 3) originality; 4) a careful and sensitive reading of text; 5) rationality; and 6) an ethical and activist stance. In this paper, critical thinking in higher education is operationally defined as: 1) originality/ creativity (Moore, 2013;Bailin et al, 1999); 2) careful and sensitive reading of text and think of beyond the text (Moore, 2013); 3) problem solving (Marin & Pava, 2017); and 4) skills which you can train to obtain (Wasserman, 1987).…”
Section: Critical Thinkingmentioning
confidence: 99%
See 1 more Smart Citation